Credit discipline and its utility for proper and prophylactic micro-financing system: assessing the global situation - Karim, A.H.M Zehadul; Abdullah, Moha Asri (2017)
To eradicate impecunious poverty throughout the world, Bangladesh first designed the procedural credit discipline system through Grameen Bank to boost the condition of rural women by deploying its own techniques innovated through a continuous ‘learning process approach’ in its specialized socio-economic and structural conditions available at the wider laboratory areas at its field level. As group-based credit policies, the microfinancing model of Grameen Bank has now been copied by as many as 80 developing nations of the world, targeting the eradication of poverty among the hard-core poor. This procedural credit discipline thus requires support for the total process of disbursement of funds and systematic repayment of loans strategically designed to make the programme sustainable. It has been cautioned that if these steps of credit discipline within the microfinancing framework are not followed properly, it may eventually destroy the main theme of credit, jeopardizing the whole system. Thus, it is now ostensibly found that many of such microfinancing programmes outside Bangladesh are now experiencing problems and difficulties due to their ignorance about the procedural techniques of credit discipline. The paper discusses the issues relating to credit discipline and suggests some recommendations for microfinancing in general including for Grameen Bank and other organizations to make credit really useful for the poor, without overburdening them with taxation.